Analysis of Fouling Pattern of Tunnel Drainage Pipe in Karst Areas - Jianbing Lv; Hao Wu; Jia Li; Xiaodong Wan; Helin Fu (Advances in Civil Engineering)
As the groundwater in karst areas is rich in calcium ions, when the groundwater flows out of the tunnel drainage pipe, calcium carbonate crystals will be precipitated and then adhere to the pipe wall, which will easily cause chemical blockage in the drainage pipe wall, thus affecting the drainage efficiency and leading to the increase of water pressure outside the tunnel lining, affecting the safety and stability of the structure. Therefore, the blockage of calcium carbonate crystals in tunnel drains is one of the most important problems for the safe and normal operation of tunnels. In order to quantify and qualify the process of crystalline blockage in the drainage system of tunnels in karst areas, this paper constructs a numerical model with coupled multiphysical fields of the flow field and particle concentration field and also combines data from indoor tests to compare and verify the simulation results and analyze the time-varying law of crystalline solids deposited on the pipe wall. In this paper, we consider the force situation of crystalline solids in the pipe by water flow, analyze the related theories, comprehensively study the migration and deposition law of crystalline particles in the drainage pipe, and establish a numerical simulation model of the pipe crystallization rate considering temperature, flow velocity and concentration of sediment particles based on ANSYS FLUENT software, and refine and analyze several parameters in the model, so that it can provide a theoretical analysis framework for the tunnel drainage pipe blockage in karst areas by providing a theoretical analysis framework.